Penerapan Model Pembelajaran Kooperatif Tipe Pair Check untuk Meningkatkan Keterampilan Menulis Puisi Siswa Kelas X SMA Negeri 2 Samalantan - Lili Yanti; Nela Yusta (Medan Resource Center, 2021)
This research is motivated by the low score of students' writing. This research is focused on analyzing the material of poetry building elements using a pair check type cooperative learning model. This research model is descriptive with a qualitative form. This research was carried out in 2 cycles. Each cycle is carried out 1 meeting. The procedure for implementing this research consists of planning, action, observing and reflecting on the results of the activities. The percentage result in the implementation of learning cycle 1 is 69.07% and in cycle 2 is 73.68%. There is an increase in the results of the implementation of learning as much as 4, 61%. Furthermore, the achievement of student learning outcomes in cycle I the average value is 71.19%, in cycle 2 it reaches 84.28%. There is an increase in the achievement of student learning outcomes as much as 13.09%.